Leaf-beetles (Coleoptera, Chrysomelidae) from the Eastern Cluj Hills „Natura 2000” Site - CRIŞAN, Alexandru; CRIŞAN, Mihaela (Studia Universitatis Babeș-Bolyai Biologia, 2015)
An investigation made in June 2014 on leaf-beetles in “Eastern Cluj Hills, Natura 2000 Site” revealed the presence of 49 species, from 6 subfamilies. Results prove an improvement of general ecological conditions of the area, the xero-mesophilous character of the vegetation and the importance of the group as indicator for human impact. Dominant species of the area, as well as rare and endangered ones, are also mentioned and discussed.